Natural Antioxidants Beneficial Effects on Anion Exchange through Band 3 Protein in Human Erythrocytes - Alessia Remigante; Rossana Morabito; Angela Marino (MDPI AG, 2019)
Band 3 protein (B3p) exchanging Cl− and HCO3− through erythrocyte membranes is responsible for acid balance, ion distribution and gas exchange, thus accounting for homeostasis of both erythrocytes and entire organisms. Moreover, since B3p cross links with the cytoskeleton and the proteins underlying the erythrocyte membrane, its function also impacts cell shape and deformability, essential to adaptation of erythrocyte size to capillaries for pulmonary circulation. As growing attention has been directed toward this protein in recent years, the present review was conceived to report the most recent knowledge regarding B3p, with specific regard to its anion exchange capability under in vitro oxidative conditions. Most importantly, the role of natural antioxidants, i.e., curcumin, melatonin and Mg2+, in preventing detrimental oxidant effects on B3p is considered.